Public Sphere Alienation: A Model for Analysis and Critique - Knobloch, Katherine (Javnost-The Public, 2011)
This paper reintroduces the theory of political alienation as a model for analysing and critiquing public sphere structures, arguing that commodified and professionalised media and organisational structures distance the general public from the production of public opinion and limit the public’s capacity to use communication for democratic empowerment. These communication norms and practices act as a counter-force to more deliberative forms of communication and (re)create five conditions of alienation – commodification, social isolation, meaninglessness, normlessness, and powerlessness – that influence what individuals know, how they interact, and who ultimately has power in the political process. Integrating literature on public opinion, deliberative democracy, mediated communication, and collective action, this paper offers an antinormative lens for critiquing currently existing practices and understanding how contemporary communication structures operate systemically.